TINJAUAN YURIDIS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK TERHADAP PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL - Aditya Farriz Novaldi (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTCrime of defamation through social media is increasingly common due to technological sophistication that can be used by every layer of society and freedom of opinion, which is not based on the ethics of using internet.This research aims: 1)To get the answer of question from writer.  2) To get answer so reserach hypotesis. The result analyze the data obtained a the following result 1) Crime of defamation regulated in pasal 310 KUHP has the concept of criminalizing every person who verbally / in writing attacks someone's honor / good name by accusing something to be publicly known, 2)  Civil law here is more directed towards material changes or money against victims or people who have been harmed. And so far this rule has been in harmony because defamation is a complaint, so in this case it returns to each person who has it, which direction the case will be brought to.